Looking back : Old Oxford Hotel (Raton Range Raton, New Mexico, 1979)
Article reads : All the necessities for the traveler -- bar, rooms and cafe -- were offered by the old Oxford Hotel, or so its sign proudly proclaimed when this early photo was made. This picture was loaned to the Range's "Looking Back" series by Victor Grant of Cimarron.
Newspaper article with photograph of Oxford Hotel
Mater List Item # 1
File location is in the New Mexico File Cabinets
Keywords: Oxford Hotel; Cimarron Hotels; Cimarron Bars; Cafes; Cimarron, New Mexico